Outcomes of a Modified CALGB 19802 Regimen in Adult Acute Lymphoblastic Leukemia - Han, A-Reum (The Korean Academy of Medical Sciences, 2008)
We analyzed the efficacy and toxicity of a modified Cancer and Leukemia Group B (CALGB) 19802 regimen in adult acute lymphoblastic leukemia (ALL). From February 2002 to August 2005, 25 adults with untreated ALL were enrolled in the study. Compared to the original regimen, the modified CALGB 19802 regimen consisted of a 4-drug induction (cyclophosphamide, daunorubicin, vincristine, and prednisone) instead of a 5-drug induction (L-asparaginase was added to the previous regimen). This was followed by high-dose methotrexate (1,000 mg/m(2)×3 days) and cytarabine (2,000 mg/m(2)×4 days) for the consolidation cycles. High-dose systemic and intrathecal methotrexate was given for central nervous system prophylaxis. Twenty-three patients (92%) achieved a complete remission (CR), and two patients (8%) had refractory disease. With a median follow-up of 21.5 months, 10 patients (40%) were alive and continued to be in CR. The 3-yr probability of an event-free survival and the overall survival were 39.0% and 47.4%, respectively. Treatment related mortality and major grade 3 to 4 neurotoxicity occurred in 1 patient and 3 patients, respectively. The modified CALGB 19802 regimen demonstrated a high remission rate and a favorable survival rate.